2014
DOI: 10.1016/j.nbd.2013.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Resolving pathobiological mechanisms relating to Huntington disease: Gait, balance, and involuntary movements in mice with targeted ablation of striatal D1 dopamine receptor cells

Abstract: Progressive cell loss is observed in the striatum, cerebral cortex, thalamus, hypothalamus, subthalamic nucleus and hippocampus in Huntington disease. In the striatum, dopamine-responsive medium spiny neurons are preferentially lost. Clinical features include involuntary movements, gait and orofacial impairments in addition to cognitive deficits and psychosis, anxiety and mood disorders. We utilized the Cre-LoxP system to generate mutant mice with selective postnatal ablation of D1 dopamine receptor-expressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…It seems likely, therefore, that increased activity in the direct pathway is in part responsible for chorea-like symptoms. In agreement with this view, targeted ablation of striatal D 1 receptors in mice is sufficient to cause gait disturbances and involuntary movements [258]. In addition, optogenetic approaches have revealed that selective activation of the striatonigral pathway is directly involved not only in movement initiation but also in motor action sequences [66, 173].…”
Section: Dopamine Modulationmentioning
confidence: 93%
“…It seems likely, therefore, that increased activity in the direct pathway is in part responsible for chorea-like symptoms. In agreement with this view, targeted ablation of striatal D 1 receptors in mice is sufficient to cause gait disturbances and involuntary movements [258]. In addition, optogenetic approaches have revealed that selective activation of the striatonigral pathway is directly involved not only in movement initiation but also in motor action sequences [66, 173].…”
Section: Dopamine Modulationmentioning
confidence: 93%
“…Increased levels of downstream signaling targets of D1 receptors in HD mice provide further evidence of elevated D1 signaling in HD (Ariano et al, ; Fusco et al, ; Roze et al, ; Spektor et al, ). Alternatively, the loss of D1 receptor‐expressing SPNs has been associated with HD symptoms as well: post‐natal ablation of dSPNs in mice results in a variety of motor symptoms including reduced locomotion, irregular gait, and tic‐like movements (Kim et al, ).…”
Section: Altered Dopamine Signaling In Hd Mouse Modelsmentioning
confidence: 99%
“…Based on the well-documented striatal disinhibition in TS (Baym et al, 2008; Mazzone et al, 2010; Wang et al, 2011; Bronfeld et al, 2013) and the finding of a selective loss in parvalbumin-positive interneurons in the striatum of TS patients (Kalanithi et al, 2005; Kataoka et al, 2010), a number of studies have begun addressing direct neurobiological hypotheses by producing selective lesions and/or pharmacological treatments in the basal ganglia. Remarkably, selective ablation of D 1 -receptor expressing striatal neurons has recently been shown to exhibit tic-like movements sensitive to treatment with the dopaminergic blocker haloperidol, as well as other locomotor impairments and striatal atrophy (Kim et al, 2014). …”
Section: Neurobehavioral Phenotypes Relevant To Tic Disordersmentioning
confidence: 99%